(untitled) (Research, Society and Development, 2026)
This article examines the impact of extending the duration of family mediation sessions at the Judicial Center for Conflict Resolution and Citizenship (CEJUSC) of the District of Fortaleza, Brazil, on the effectiveness of judicial agreements from 2021 to 2024. The study addresses the following research question: to what extent does increasing session duration influence the effectiveness of family mediation? The objective is to analyze the relationship between session length and agreement outcomes. This is an applied study with a qualitative-quantitative approach, adopting a descriptive and analytical design, based on statistical analysis of institutional data, participant observation, and literature review. The study investigates how available time affects the quality of listening, emotional management, the use of consensual dispute resolution techniques, and the achievement of lasting agreements. The findings indicate a progressive increase in agreements following the implementation of sessions lasting at least two hours, with consistent results across the analyzed period: 1,357 agreements in 2021; 1,683 in 2022; 2,636 in 2023; and 2,809 in 2024. These results suggest that time functions as a structuring element of the mediation process, enabling deeper narrative exploration and strengthening the parties’ decision-making autonomy. It is concluded that proper time management constitutes an essential public policy for ensuring the quality, effectiveness, and legitimacy of family mediation within CEJUSCs.